Foreign Aid and Its Effectiveness in Sub-Saharan Africa: Theoretical Criticisms and Empirical Facts - (:unkn) unknown (My University, 2017)
The chapter analyses aid flows to Sub-Saharan Africa (SSA) and their implications for its economic development. SSA economies are characterised by an important share of primary commodities in their exports, which induces the volatility of revenues and therefore fiscal deficits that are a key factor of the dependence on foreign aid. The chapter shows that in the 21st century the negative effects of aid in SSA are viewed as more significant than the positive ones, via a comprehensive review of the debates on aid effectiveness in SSA. Indeed, aid is subject to increasing theoretical criticisms: though aid was supposed to indisputably contribute to growth, the weak relationships between aid and growth are increasingly underscored in the theoretical and policy literature, together with the negative macroeconomic effects of aid, in particular those created by aid dependence – particularly important in SSA -, aid having also a negative impact on domestic institutions in aid-dependent countries. Other negative effects stem from the characteristics of the aid relationship itself, notably the problems inherent in conditionality, the diverging incentives in the ‘aid game’, aid volatility and donors’ poor coordination. Finally, ‘new’ donors from emerging countries participate in aid flows to SSA, and their impacts on SSA economies appear to converge with those of ‘traditional’ donors (e.g., European countries, the United States). China’s development cooperation, however, differs from ‘traditional’ donors due to its lack of conditionality and its reliance on ‘resources-for-infrastructure’ contracts.
Keywords: African Research